Spatial Analysis of the Cooling Effects of Green and Blue Infrastructure Using Remote Sensing: A Case Study in Amasya (Türkiye) - Meltem GÜNEŞ TİGEN (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The urban heat island (UHI) effect is a major environmental challenge driven by rising surface temperatures due to urbanization. This study analyzes the spatial distribution of UHI in Amasya’s city center and evaluates the temperature-regulating functions of green and blue infrastructure. Land Surface Temperature (LST) data derived from Landsat 9 satellite imagery were integrated with NDVI (Normalized Difference Vegetation Index) and buffer analyses of water bodies to examine spatial thermal variations. The results reveal an average surface temperature of 31.93°C in the urban core, compared to 30.78°C in rural areas, highlighting an urban-rural temperature disparity exceeding 1°C. Although rural zones are generally cooler, agricultural lands with sparse vegetation exhibit peak temperatures of up to 42.57°C. The cooling effect of green infrastructure is evident, as densely vegetated regions experience a decline in surface temperatures, averaging 23.64°C. Likewise, blue infrastructure plays a significant role in thermal regulation, as surface temperatures near the Yeşilırmak River are approximately 3°C lower. Analysis of a 40-meter buffer zone along the river, considering its mean width, indicates an average LST of 28.82°C. The findings emphasize the crucial role of green and blue infrastructure in alleviating the UHI effect and highlight the necessity of integrating these elements into sustainable urban planning strategies.